2021
DOI: 10.1021/acs.jpca.1c08631
|View full text |Cite
|
Sign up to set email alerts
|

Ground and Electronically Excited States of Main-Group-Metal-Doped B20 Double Rings

Abstract: Ab initio coupled-cluster, electron propagator, and Møller–Plesset second-order perturbation theory calculations are utilized to analyze the low-lying electronic states of several metal-doped B20. In the ground state, the presently focused AB20/EB20 (A = Li, Na, and K; E = Mg and Ca) consist of charge-separated A+B20 –/E2+B20 2– frameworks. The excited electronic states of AB20 and EB20 + were analyzed by computing the vertical electron attachment energies (VEAEs) of AB20 + and EB20 2+. In several excited stat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 75 publications
0
2
0
Order By: Relevance
“…Previous studies have suggested that the main-group-metal-centered monocyclic rings tend to be located as local minima rather than global minima . Additionally, the heavier Ae atoms with a large radius size are usually located at the off-centered position in the tubular boron clusters . Consequently, we chose two heavier Ae atoms as dopants in the boron clusters to obtain highly symmetric and stable candidates.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Previous studies have suggested that the main-group-metal-centered monocyclic rings tend to be located as local minima rather than global minima . Additionally, the heavier Ae atoms with a large radius size are usually located at the off-centered position in the tubular boron clusters . Consequently, we chose two heavier Ae atoms as dopants in the boron clusters to obtain highly symmetric and stable candidates.…”
Section: Resultsmentioning
confidence: 99%
“…67 Additionally, the heavier Ae atoms with a large radius size are usually located at the offcentered position in the tubular boron clusters. 68 Consequently, we chose two heavier Ae atoms as dopants in the boron clusters to obtain highly symmetric and stable candidates. Following the above electron counting rule (2x + 12/20/26 + 2y), four extra electrons should be counted due to the presence of two Ae atoms.…”
Section: ■ Results and Discussionmentioning
confidence: 99%